ANALISIS KOMPARATIF DIMENSI KUALITAS DATA PADA SISTEM INFORMASI PUBLIK: STUDI SINTESIS LITERATUR 2015–2024 - Ayu Anggraini Hulu; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to comparatively analyze various dimensions of data quality applied in public information systems through a literature synthesis approach during the period 2015– 2024. Data quality is a crucial element in ensuring the reliability of public information systems used by government agencies, public service institutions, and other public sectors. This study uses a systematic literature review method for 40 scientific journals obtained from databases such as Google Scholar, Scopus, and ScienceDirect. The results of the study show that there are four dimensions of data quality that are most dominantly used, namely accuracy, completeness, consistency, and timeliness. However, there are variations in the application and emphasis of these dimensions depending on the context and purpose of the information system being studied. In addition, a research gap was also found in the dimensions of data integrity and accessibility which are still rarely discussed in depth. These findings are expected to be the basis for the development of a more reliable public information system that is oriented towards data quality.